IMPLEMENTASI NILAI KARAKTER DEMOKRATIS PADA SISWA: ANALISIS KEGIATAN PRAMUKA DI MAN NURUL HUDA SEMARANG - Amrullah, M. Faiz Arsyadani; Sudrajat, Rahmat; Suprijanto, Agus (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2024)
The value of democratic character is very crucial in every student, because with democratic character, students will be able to interact with local residents, which requires a sense of tolerance and independence, so that democratic character must be applied to students through learning activities. The aim of this research is to determine the implementation of students' democratic character values in scouting activities at MA NU Nurul Huda Semarang. This research uses a descriptive method with a qualitative approach. The hypothesis in this research is that it is hoped that students will have the attitude to think and act by assessing their own rights and obligations with those of others. The findings of this research prove that the implementation of students' democratic character values in scout activities has several influencing factors, both supporting factors and inhibiting factors which of course become evaluations for research objects that must be addressed in order to achieve maximum results. The results of the research prove that MA NU Nurul Huda has implemented the democratic character values of students in scouting activities which were carried out using varied methods, namely through selecting new pre-funding activities, forming activity committees, and joint discussion activities